Needs Analysis on the Development of Integrated GITTW Hybrid Learning Model in the Learning of Biology at Senior High School - Listiana, Lina; Daesusi, Ruspeni (Universitas Muhammadiyah Surabaya, 2022)
The rapid development of technology in the era of globalization affects the world of education. As a result, learning must be able to adapt by utilizing technology. in line with this, there are problems in learning biology such as the lack of understanding a biological concepts, learning motivation and learning independence of students. As the consequency, the learning outcomes is declining. This study aims to determine the needs and potentials of teachers and students in learning biology as the basis for developing an Integrated GITTW (Group Investigation and Think Talk Write) Hybrid Learning Model strategy in Biology learning. This research is a descriptive type with the research subjects of teachers and students of grade X science at Senior High School in the city of Surabaya. Data were collected through observation, documentation, questionnaires and interviews. The results of the study reveal that teachers and students need the learning innovations by utilizing learning technology. The integration of technology in learning makes it easier for students to obtain information from various media and learning resources. The hybrid learning model integrated with the GITTW strategy with Moodle-based media makes learning more effective, efficient, and interesting and according to students' interests in using media such as smartphones and laptops. Through the model that will be developed, learning problems in comprehending biological concepts, learning activities and motivations as well as students' learning independence that are lacking in biology learning are expected to be resolved. Based on this fact, it is necessary to develop a hybrid learning model that integrates the GITTW strategy in biology learning.